2010
DOI: 10.1111/j.1600-0404.2009.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetranectin and apolipoprotein A-I in cerebrospinal fluid as potential biomarkers for Parkinson’s disease

Abstract: Our preliminary results suggest that tetranectin and apoA-I may serve as potential biomarkers for PD, though further validation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
(60 reference statements)
2
38
0
Order By: Relevance
“…Immunohistochemistry showed tetranectin immunoreactivity in neurons and dendrites, and a lack of staining in glial cells in the cerebrum and cerebellum, and the source of tetranectin in the CSF is believed to be the central nervous system [28]. Our previous study demonstrated that tetranectin was present at reduced levels in PD patients in comparison to normal controls [29]. In the present study, we further confirmed these results and found that tetranectin levels were significantly elevated after STN DBS.…”
Section: Discussionsupporting
confidence: 80%
“…Immunohistochemistry showed tetranectin immunoreactivity in neurons and dendrites, and a lack of staining in glial cells in the cerebrum and cerebellum, and the source of tetranectin in the CSF is believed to be the central nervous system [28]. Our previous study demonstrated that tetranectin was present at reduced levels in PD patients in comparison to normal controls [29]. In the present study, we further confirmed these results and found that tetranectin levels were significantly elevated after STN DBS.…”
Section: Discussionsupporting
confidence: 80%
“…The biological function of TN has not been fully elucidated, though it is thought to play an important role in the regulation of proteolytic and fibrinolysis processes by binding to plasminogen. It is also believed to play a critical role in mineralization during osteogenesis and in myogenesis during embryonic development [19]. Furthermore, TN has been implicated as a potential biomarker in conditions ranging from cancer to Parkinson's disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…ApoA1 together with another apolipoprotein, apoE are responsible for lipid transportation in the brain. Lower levels of one isoform of apoA1 and tetranectin are reported in the CSF of PD patients, suggesting that apoA1 is a potential biomarker for PD (Wang et al, 2010; Swanson et al, 2015). ApoA1 cannot be secreted from neurons, but as the main component of HDL, it is required for cholesterol transportation to the brain.…”
Section: Neurochemical Biomarkersmentioning
confidence: 99%